Beyond One-Size-Fits-All: Context-Sensitive Approaches to Local Government Improvement in Developing Countries - Rahmat Aminullah Muhadli; Harry Nenobais; Johanna Novita (Darul Yasin Al Sys, 2026)
Although context-sensitive approaches to local governance have received increasing attention in development studies and comparative public administration, research integrating structural, relational, and normative dimensions across developing-country contexts remains limited. This study aimed to examine how contextual conditions shape local government improvement and to develop an integrative theoretical framework explaining variations in local governance outcomes across developing countries. A qualitative comparative theoretical synthesis was conducted using the literature compiled by de Vries, Reddy, and Haque (2008), supplemented by relevant empirical and theoretical studies published between 2008 and 2023. The analysis encompassed evidence from Latin America, Sub-Saharan Africa, and South Asia and focused on three interrelated dimensions: structural conditions, relational dynamics, and normative conditions. The findings indicate that formal decentralization does not automatically produce equivalent improvements in local government capacity or performance. Instead, governance outcomes vary according to fiscal and administrative capacity, intergovernmental relations, territorial and institutional configurations, citizen participation, and the involvement of non-state actors. The synthesis further demonstrates that community-centred, state-centred, market-centred, radical, and network perspectives each explain important yet partial dimensions of local governance. Integrating these perspectives, the study proposes a multi-centred theory of local governance that combines local autonomy and accountability, context-sensitive central oversight, conditional market mechanisms, multi-actor collaboration, and sensitivity to institutional and territorial conditions. The study concludes that local government improvement requires governance reforms adapted to specific political, institutional, social, fiscal, and territorial contexts rather than the uniform replication of standardized best practices. This study contributes an integrative framework for comparative local governance research and provides practical guidance for policymakers and development institutions in designing context-sensitive decentralization and local government reforms. Future research should empirically test and refine the proposed framework across a broader range of local government settings.